Hematological Profile of Healthy Pregnant Females in Association with Parity - Inam-ul-Haq,Muhammad Awais Ahmed,Bushra Anwar, Muhammad Amer Saleem, (Journal of Rawalpindi Medical College, 2013)
Background: To determine the haematological profile of normal pregnant females. Methods: In this cross sectional study 100 healthy young pregnant females, during third trimester of pregnancy, were included. Subjects were divided into two sub-groups, with 68 being multigravida and remaining 32 primigravida. Haematological analysis was undertaken. The mean and standard deviation of all the parameters were calculated and compared in association with parity and t-test was employed. Results: The age range of the subjects was 18-38 years. Majority of the parameters did not show any significant difference but three parameters i.e., serum ferritin, serum transferrin receptors and transferrin receptor-ferritin index deviated from the usual trend of the others and showed a statistically significant difference between the two groups (p<0.05).In cases with pacing of pregnancy upto I year, 57.1% showed low serum ferritin, while in those with spacing of pregnancy more than 2 years, 12.8% showed low serum ferritin . Conclusion: There is a need to develop reference haematological values in association with parity as some of the parameters vary significantly with it. Narrower is the spacing between pregnancies, more pronounced is the fall in ferritin levels.